Evaluasi Guru Bersertifikasi pada Gugus I Kecamatan Lolong Guba Kabupaten Buru - Nurbai Saparwati Luhulima; Izaak HendrikWenno; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to evaluate certified teachers in preparing and planning lessons, evaluating certified teachers in managing classrooms, evaluating certified teachers in carrying out the learning process, evaluating certified teachers for their responsibilities and professionals in learning. This research was conducted at SD Negeri 2 Lolong Guba, SD Negeri 4 Lolong Guba, SD Negeri 5 Lolong Guba, SD Al-Hilaal Wabloy and SD Al-Hilaal Italahin involving 2 teachers in each school. The overall results of the evaluation of Charlotte Danielson model-certified teachers at SD Negeri 2 Lolong Guba domain 1 are (100%) very good category, domain 2 is (96.5%) very good category, domain 3 is (86.5%) very good category and domain 4 is (97%) very good category. SD Negeri 4 Lolong Guba domain 1 is (100%) very good category, domain 2 is (96.5%) very good category, domain 3 is (76.5%) good category, domain 4 is (94%) very good category. SD Negeri 5 Lolong Guba domain 1 is (100%) very good category, domain 2 is (90%) very good category, domain 3 is (76.5%) good category and domain 4 is (94%) very good category. SD Al-Hilaal Wabloy domain 1 is (100%) very good category, domain 2 is (80%) good category, domain 3 is (70%) sufficient category and domain 4 is (94%) very good category. SD Al-Hilaal Italahin domain 1 is (63.5%) category is good enough, domain 2 is (70%) category is good enough, domain 3 is (67%) category is quite good.